Pengaruh Total Aset, Aset Tetap dan Debt Ratio Terhadap Durasi Audit Pada Perusahaan Sektor Otomotif Periode 2021-2024 - Ariana Daania Hermawan; Nudhar Cahyani; Agnes Cloudia; Andi Nurnaflah Anastasya Ramadani; Ricky Bryan D.P. Tampubolon (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2026)
This study examines the influence of Total Assets, Fixed Assets, and the Debt Ratio on Audit Duration in automotive sector companies listed on the Indonesia Stock Exchange during the period from 2021 to 2024. The sample consists of thirty-five observations from nine companies selected using purposive sampling. The analysis was conducted through classical assumption testing and multiple linear regression, including simultaneous testing, partial testing, and the assessment of the coefficient of determination. The findings indicate that Total Assets have a negative effect on Audit Duration, while Fixed Assets and the Debt Ratio have positive effects. The three variables also show a simultaneous influence on Audit Duration. Overall, the research model explains a portion of the variation in audit duration, although other factors such as the quality of internal controls, transaction complexity, and auditor policies may also contribute beyond the scope of this study.